Assessing osteopenia and osteoporosis with dual-energy x-ray absorptiometry studies in Fabry disease - Shmara, Alyaa; Lee, Grace; Mgdsyan, Mania; Hall, Kathy; Sadri, Nadia; Martin-Rios, Angela; Valentine, Kelsey; Kain, Tatiana; Pahl, Madeleine; Polgreen, Lynda E.; Kimonis, Virginia (Orphanet journal of rare diseases, 2025)
Background Fabry disease (FD) is a rare multi-systemic lysosomal storage disease that affects the heart and kidneys most significantly. An underappreciated manifestation of FD is reduced bone mineral density. Currently, there are no specific guidelines for routine bone density assessments, and treatment of osteoporosis and osteopenia in FD. Materials and methods To ascertain the frequency of low bone mineral density in FD we studied dual-energy x-ray absorptiometry (DXA) scans obtained as part of routine care from a cohort of 25 individuals followed at the University of California—Irvine Medical Center for the period 2008–2023. The most recent BMD results for the lumbar spine and femoral neck were collected from 12 males and 13 females to examine the prevalence of low bone mineral density. The lowest Z- and/or T-scores of either lumbar spine or femoral neck were selected for analysis. Demographic factors, disease and ERT status, and other laboratory values were collected concurrently (within ± 9 months) with DXA scan results and were analyzed with Z- and T-scores to assess for correlations. In our cohort the mean age was 51 years (median 56 years, range 18–77 years). The Z-scores for all participants and T-scores from postmenopausal women and men ≥ 50-year-old were analyzed and correlated with various measures including disease duration, BMI, renal function (measured by eGFR), plasma GL3, Lyso-GL3, calcium, vitamin D, and alkaline phosphatase levels. These parameters were concurrent with DXA scan results. Results The average Z-score for all the participants was −1.2 ± 1.3 (range −4.6 to 1.6). Twenty-four percent of all participants ( n = 6) had significantly low Z-scores ≤ −2.0. To identify the frequency of subjects with osteopenia, defined as T-score between −1.0 and −2.5 and osteoporosis defined as T-score < −2.5, T-scores were analyzed in postmenopausal women ( n = 8) and men 50 years and older ( n = 7). Of these 15 individuals, average T-score was −2.2 ± 1.3 (range −5.4 to 0.3), and 86.7% ( n = 13) had abnormal results (osteopenia and osteoporosis), 53.3% ( n = 8) had osteoporosis and 33.3% ( n = 5) had osteoporosis. We found a significant difference in Z-scores between male (−1.98 ± 1.33) and female patients (−.45 ± 0.82) t (23) = 3.487 ( p = < 0.001). We did not find any differences in z-scores between different ethnic backgrounds. There was a strong negative correlation between Z-scores and Lyso-GL3 levels [r (15) = −.72, p = .001] and a moderate positive correlation between Z-scores and body mass index (BMI) [r (23) = .43, p = .033]. No correlation was found between Z-scores and calcium levels. There is a strong negative correlation between T-scores and Lyso-GL3 levels [r (8) = -.86, p = .001] and a negative correlation between T-scores and participants’ ages at the time of DXA [r (13) = −.57, p = 0.028]. There is a positive correlation between T- scores and calcium levels [r (12) = .58, p = 0.030]. No significant correlation was observed between T-scores and BMI. There was no correlation between Z or T- scores and disease duration, duration of ERT use, renal function (measured by eGFR), GL3, creatinine, alkaline phosphatase levels, or their use of vitamin D or concomitant antiepileptic medications. Conclusion The findings of this cohort highlight the high prevalence of low bone mineral density in FD and correlations of low Z and T- scores with elevated levels of Lyso-GL3, and low calcium levels. We did not find correlations with renal function, and vitamin D levels. We discuss etiology, prevention, and treatment strategies for osteopenia/osteoporosis in Fabry disease.